Prevalence and Genetic Diversity of DHFR Gene Polymorphisms in Plasmodium falciparum from Southern Côte d’Ivoire: Implications for Antimalarial Drug Resistance - Oléfongo, Dagnogo; Berenger, Ako Aristide; Brice, Bla Kouakou; Noel, Dago Dougba; David, Coulibaly N'golo; Baba, Coulibaly; André, Touré Offianan; Joseph, Djaman Allico (Research Perspectives of Microbiology and Biotechnology Vol. 7, 2024)
This study aimed to determine the prevalence of the Asn-108 marker in Southern Côte d'Ivoire. Malaria remains a major public health issue, particularly in sub-Saharan Africa. The dihydrofolate reductase (DHFR) gene in Plasmodium falciparum plays a critical role in the parasite’s resistance to sulfadoxine-pyrimethamine (SP), a widely used antimalarial drug. Mutations in pfdhfr and pfdhps genes confer resistance to pyrimethamine and sulfadoxine respectively, with an in vitro decrease in P. falciparum sensitivity related to the number of mutations in each gene. In fact, since 2005, Côte d'Ivoire has adopted new strategies for malaria management including free provision of Artemisinin-based Combination Therapy (ACT) to children less than five years of age and sulfadoxine-pyrimethamine (SP) as Intermittent Preventive Treatment (IPT) for pregnant women. However, the introduction of ATCs raises concerns about the extensive use of cheap SP which could increase Plasmodium falciparum resistance level to SP. After obtaining consent, blood samples were collected in Anonkoua-kouté, Port-Bouët, and Ayamé sites from 180 patients over 2 years of age and having simple P. falciparum malaria. P. falciparum genomic DNA extracted from these samples was amplified by nested-PCR with pfdhfr specific primers. The amplification products were revealed by electrophoresis on 1.5% agarose gel and then sequenced according to the Sanger method. After sequencing, the prevalence of mutation points associated with P. falciparum resistance to pyrimethamine was determined. For the three study sites, 180 DNA fragments, of which 165 (165/180 or 91.66%) were successfully sequenced. A high prevalence of triple-mutant P. falciparum parasites reduces the efficacy of sulfadoxine-pyrimethamine as an intermittent preventive treatment against malaria in infants and children. Analysis of the 165 sequences indicated a prevalence of 61.29% (76/124) of the Asn-108 mutant allele versus 17.41% (27/155) of the wild-type Ser-108 allele. Results also indicated that the prevalence of Ser-108-Asn mutation was 69.07, 69.04 and 82.75% for Anonkoua- Kouté, Port-Bouët and Ayamé, respectively. More than a decade after the adoption of SP as IPT for pregnant women, the prevalence of the marker Asn-108 was relatively high in Anonkoua-kouté, Port- bouët and Ayamé. The study revealed an increase in potentially pyrimethamine-resistant isolates despite the withdrawal of SP as a first-line antimalarial treatment. These high proportions of known mutations in the pfdhfr gene could be in favour of a decrease in the SP efficacy in Côte d'Ivoire.